2003
DOI: 10.1007/s00216-003-1789-1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of low molecular weight organic acids in soil, plants, and water by capillary zone electrophoresis

Abstract: Determination of low molecular weight organic acids in soils and plants by capillary zone electrophoresis was accomplished using a phthalate buffer and indirect UV detection mode. The influence of some crucial parameters, such as pH, buffer concentration and surfactant were investigated. A good separation of seven organic acids was achieved within 5 min using an electrolyte containing 15 mmol L(-1) potassium hydrogen phthalate, 0.5 mmol L(-1) myristyltrimethylammonium bromide (MTAB), and 5% methanol (MeOH) (v/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…In our separate study (Li et al, 2003) the concentrations of acetic, lactic, malic and formic acids in rhizosphere soil and plant roots were determined, which ranged from below the detection limits of capillary zone electrophoresis to several mM. Other studies have also reported that the most abundant monocarboxylic acids (such as formic, acetic and propionic acids) were up to 1 mM in soil solutions (Jones, 1998;Strobel, 2001).…”
Section: Optimization Of Rhizosphere-based Extraction Proceduresmentioning
confidence: 78%
“…In our separate study (Li et al, 2003) the concentrations of acetic, lactic, malic and formic acids in rhizosphere soil and plant roots were determined, which ranged from below the detection limits of capillary zone electrophoresis to several mM. Other studies have also reported that the most abundant monocarboxylic acids (such as formic, acetic and propionic acids) were up to 1 mM in soil solutions (Jones, 1998;Strobel, 2001).…”
Section: Optimization Of Rhizosphere-based Extraction Proceduresmentioning
confidence: 78%
“…The total concentration of LMOWAs and their ratio were chosen based on their abundance in the rhizosphere zone. Acetic and lactic acids are the highest concentrations of all five LMWOAs because these two organic acids are more likely to originate from rhizosphere bacteria (Jones, 1998) and are the most abundant carboxylic acids in soil solution (Strobel, 2001;Li et al, 2003). Bioavailability of soil metals is the result of a combination effect of rootesoilemicrobe interaction occurring in the rhizosphere soil zone, in which LMWOAs are the primary factor involved in the metal adsorption by roots (Wang et al, 2004b;Han et al, 2005).…”
Section: Preference Of the Rhizosphere-based Methods Over Other One-stmentioning
confidence: 99%
“…In our previous study it was demonstrated that acetic, lactic, malic and formic acids were dominant in plant roots and in the rhizosphere soil, ranging from several mM to several hundreds of mM, respectively (Li et al, 2003;Han et al, 2005). In order to simulate the content gradient of LMWOAs from root surface to soil solution (Cies´lin´ski et al, 1998;Fox and Comerford, 1990) and to use a short-term extraction for simulation of longterm reaction in the rhizosphere environment, the use of a mixture of total 10 mM of acetic, lactic, citric, malic, and formic acids at the molar ratio of 4:2:1:1:1 as an extractant was proposed as reasonable.…”
Section: Bioavailability Of Metals In Soils To Barleymentioning
confidence: 99%
See 1 more Smart Citation
“…The first two steps of BCR method and a single extraction procedure were adopted in this study. Among the reported LMWOAs, acetic acid, formic acid, citric acid and malic acids were frequently found to be the abundant organic acids (Jones, 1998;Li et al, 2003). The detailed extraction conditions are listed in Table 2.…”
Section: Fractionation Of Metals In Soilmentioning
confidence: 99%